La Tinta Bay Chacachacare, Trinidad - (:unkn) unknown (Muir Marshall and Co.,[Trinidad and Tobago], 2011)
This postcard features a craggy headland and a sparse beach. The name of the addressee is illegible but the original destination of the postcard is Michigan, United States of America and affixed is penny Trinidad postage stamp.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; 1907; Beachgoers--Trinidad and Tobago; Islands--Trinidad and Tobago; Bays--Trinidad and Tobago; Chacachacare